Gender in Philosophy and Law - Palazzani, Laura. author. (orcid)0000-0001-9870-1304 Link aut Link
XIV, 116 p.
Keywords: This book is an introductory systematic framework in the complex and interdisciplinary sex/gender debate, focusing on philosophy of law.The volume analyses the different theories that have dealt with the gender category, highlighting the conceptual premises and the arguments of the most influential theories in the debate, which have had repercussions on the field of the ethical and juridical debate (with reference to intersexuality, transsexualism, transgender, homosexuality). The aim is to offer a sort of conceptual orientation in the complexity of the debate, in an effort to identify the various aspects and development processes of the theories, so as to highlight the conceptual elements of the theorisations to grasp the problem areas within them. It is therefore an overall synthetic and also explicative analysis, but not only explicative: the aim is to outline the arguments supporting the different theories and the counter-arguments too, for the purpose of proposing categories to weigh up the elements and to take one’s own critical stance, with a methodological style that is neither descriptive nor prescriptive, but critical. .